BARBERS' EDUCATION; A WINDOW TO IMPROVE THE PUBLIC ABOUT SKIN DISEASES - Aboud, Daifullah Al; Aboud, Khalid Al; Ramesh, V (Journal of Ayub Medical College Abbottabad, 2007)
A barber's profession is closely linked to the beliefs of an individual. Many people visit the barber at regular intervals and spend a significant time in shop, either waiting for their turn to come or during cutting and/or shaving of their hairs. The time spent in the shop is when people informally exchange talks with each other which include the customers themselves and the barber. The opinion given by the barber is often taken for granted since in the eyes of the customers the barber speaks through professional experience, practical observation, and instills confidence by relating the true experience of others too. These facts assume significance if one thinks of utilizing the barber's shop for public health education. Some skin disorders may have escaped the attention of the client and may be pointed out by the barber while doing his job. Alopecia areata, for example, can be first detected by the barber if the alopecic patch is small or in an area not easily viewed by the affected person. Other dermatological conditions like pediculosis might be seen first by barbers. Also, the improper techniques by the barbers might exacerbate existing skin disorders. For example, shaving with less foam or gel, and shaving against the direction of hair may worsen pseudofolliculitis barbae. In some rural areas, barbers are also involved in medical and surgical procedures like circumcisions, tattooing, and cupping. In addition, some new barbers are performing what they believe as peeling or cosmetic techniques. The above unlicensed activities by barbers are being done without knowing important health principals. Therefore, some people have complications due to these practices. One of these complications is the cross infection, namely microbial skin diseases and bloodborn disease transmission in developing countries 1. Public education is an important resource to improve the health of people in general. It helps to narrow the knowledge gap between doctors and ordinary people. Many myths and wrong ideas are being propagated by people in the absence of efficient health education. People may panic about something transmitted by the media if there is no health education or a source of information to address the correct data. A lot of myths and misconceptions need to be addressed in connection with skin disorders. This problem extends to family physicians too who may hold these misconceptions.2 With advancement of our profession, and proliferation of many government and nongovernmental organizations, we must strive to improve public education. The American Academy of Dermatology (AAD) has taken many steps in this regard, for example screening programs for skin tumors and publishing public pamphlets about these skin disorders. One of the authors (KA) asked barbers randomly about some basic facts related to dermatology and found that all of them were unaware, not to mention that some of them delivered absolutely erroneous views, e.g. one barber guaranteed that androgenetic alopecia could be cured by applying a special oil. We believe that barber shops should be utilized for imparting health education and we exhort health related societies to: 1. Arrange short courses for barbers 2. Put educational pamphlets in barber shop 3. Make posters on the walls of barber shop. This model of promoting public health has been exploited in South Carolina through the extended use of not only barbers' shops but also beauty saloons.3 The themes for health awareness are created by a dedicated team of workers whose goal is to disseminate disease prevention measures to places where people frequent. Cooperation between health authorities and municipalities is to be encouraged. Health authorities should provide strict supervisions on the barbers' shops, and in particular,